Legal Consequences for Children Who Commit Criminal Acts of Terrorism Based on Law Number 5 of 2018 Concerning the Eradication of Criminal Acts of Terrorism - Andi Rief Irfandi; Anak Agung Gede Putra Arjawa; Ida Bagus Anggapurana (Yayasan Adra Karima Hubbi, 2023)
Terrorism is an extraordinary crime (Extra Ordinary Crime), the international world created the concept of constitution through international conventions, namely the